Mastering Brexits through the ages : entrepreneurial innovators and small firms the catalysts for success - Culkin, Nigel; Simmons, Richard (Emerald Publishing Limited, 2018)
Brexit is arguably the most significant UK foreign and economic policy event since at least 1945. Opinion is bitterly divided between whether to leave, when to leave, how to leave and even on what Brexit is. 'Mastering Brexits Through the Ages: Entrepreneurial Innovators and Small Firms - The Catalysts for Success' explores these dynamics through the lens of three previous 'Brexits' the end of Roman Britain, the Henrician Reformation, and the Elizabethan age. Using multiple historical epithets, it illuminates insights into innovation needs, smaller firm growth, previous step change events and related economic understanding. This book paints a broad picture of possible UK post-Brexit landscapes.Echoing an earlier European Treaty (Versailles, 1919), fourteen action points that can contribute to mitigating downside risks and making post Brexit UK a leading force in the Global Economy are identified. At all times, dynamic entrepreneurs and small companies are at the centre of the narrative.This book is both a key contribution to understanding implementation risks and to identifying what a 'winning' post-Brexit UK economy should look like. Drawing on extensive research, the book identifies the strategic framework and associated practical measures needed to realise a positive outcome. It concurrently analyses Brexit mythology through carefully unpicking and demystifying complexities, anticipated Brexit risks, impacts, implications and unknowns. A book for academics, policy makers, advisers and interested bystanders alike.